Exploring Deep-Rock Mechanics through Mechanical Analysis of Hard-Rock In Situ Coring System - Jianan Li; Heping Xie; Ling Chen; Cong Li; Zhiqiang He (Advances in Civil Engineering)
Exploration of deep-rock mechanics has a significant influence on the techniques of mining and rock mechanics. Rock coring technique is the basic method for all rock mechanics study. With the increase of the drilling depth and increasing strength of the hard rock, how to obtain high-quality rock core through various coring techniques is an eternal work. Here an innovative method is applied to design the new coring system to maximize the efficiency of operation. The stress conditions or parameters of rock core in the coring are analyzed, and the mechanism of the core with in situ stress is shown in this paper. The conflict of the core and coring tool chamber is proposed for the innovative design. The innovative design method is fulfilled by the theory of inventive problem solving (TRIZ). An improved coring system for the full-length core with in situ stress was obtained with the solutions of improved coring mechanism, cutting mechanism, and spiral drill pipe.